Differentiated Learning Practices In Islamic Religious Education At Junior High School: Implementasi Pembelajaran Berdiferensiasi Pada Pendidikan Agama Islam Di Sekolah Menengah Pertama - Hartina Hartina; Mania Mania; Mardiah Mardiah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Education systems increasingly recognize learner diversity as a central concern in classroom practice. Specific Background: In Islamic Religious Education and Character Education, uniform instructional approaches remain prevalent, limiting accommodation of students’ varied readiness, interests, and learning styles within the Merdeka Curriculum framework. Knowledge Gap: Empirical descriptions of how differentiated learning is planned, enacted, and evaluated in Islamic Religious Education at the junior high school level remain limited. Aims: This study examines the implementation of differentiated learning in Islamic Religious Education and Character Education at SMP Negeri 2 Bulukumba. Results: Using a qualitative case study design, data from observations, semi-structured interviews, and documentation reveal that teachers conduct diagnostic assessments to map students’ readiness, interests, and learning profiles, followed by differentiation of content, process, and product through varied strategies, media, grouping patterns, and assessment forms. Instructional practices demonstrate adaptive classroom management and student-centered learning, although challenges arise from limited instructional time, large class sizes, and varying levels of teacher understanding. Novelty: The study presents a detailed depiction of differentiated learning across planning, implementation, and evaluation stages within Islamic Religious Education aligned with Merdeka Curriculum principles. Implications: These findings underscore the need for sustained professional support, practical training, and institutional facilitation to strengthen differentiated learning practices that support inclusive, flexible, and character-oriented instruction. Highlights • Diagnostic assessment guides differentiated planning based on readiness, interest, and learning profiles• Instructional practices vary content, process, and product within Islamic Religious Education classrooms• Evaluation employs flexible and authentic assessment aligned with student diversity Keywords Differentiated Learning; Islamic Religious Education; Merdeka Curriculum; Learning Styles; Qualitative Case Study